Computer-Based Instrument for Evaluation of Professional Teacher Program (PPG) - Roza, Yenita; Siregar, Syarifah Nur (Proceedings of the UR International Conference on Educational Sciences, 2018)
The Teacher Professional Program (PPG) is one of the program created by Government in empowering teachers and teachers candidates in conducting a good teaching. The curriculum and evaluation for this program was developed by the government. There are 12 aspects that will be evaluated for each participant, an evaluation forms are available to be used by the instructor. The problem encounter by instructor in doing evaluation is time consuming and calculation error because the number of aspect to fill in the form. This research is aim to developed computer-based evaluation instrument that not only easier to fill but also less time consuming and prevent the error calculation. This development used 4D Model which included define, design, developed and dissemination. Analysis of available instrument is done in defining phase, it found that the indicator of scoring is needed to have a better grading. Based on this finding, scoring indicators are developed along with computer based form in design and develop phase. There are nine form were developed by adding the indicators and revising the appearance, five of them used for document analysis, four used for observation. The computer-based evaluation forms that been developed are recommended to used by the PPG isntructors.